Cover Image. (12th August 2020) - Taheri‐Ledari, Reza; Valadi, Kobra; Maleki, Ali
Abstract : The cover image is based on the Research Article High‐performance HTL‐free perovskite solar cell: An efficient composition of ZnO NRs, RGO, and CuInS2 QDs, as electron‐transporting layer matrix by Reza Taheri‐Ledari et al., https://doi.org/10.1002/pip.3306 .